Association between ABO blood groups and hematological myeloid neoplasms in adolescents and adults - Zhou, Miao; Li, Tongyu; Sun, Yongcheng; Ouyang, Guifang; Zhuang, Wanchuan; Zhang, Ping (Frontiers in Medicine, 2024)
Background Prior research suggests a potential link between ABO blood types and susceptibility to various malignancies. The correlation between ABO blood types and hematological myeloid neoplasms, however, remains inadequately explored. Objective This study investigates the association between ABO blood groups and the incidence of hematological myeloid neoplasms in adolescents and adults. Methods In this retrospective clinical study, 1,022 adolescent and adult cases of myeloid neoplasms diagnosed at our institution were initially considered. After excluding conditions potentially linked to ABO blood types from prior studies, 792 eligible cases were analyzed. These cases were categorized based on disease subtypes and compared with a control group for blood type distribution. Results Our findings reveal a significantly higher prevalence of blood type A in patients with myeloid neoplasms compared to the control group, except for chronic myelocytic leukemia and myeloproliferative neoplasms. Conversely, the prevalence of blood type AB in myeloid neoplasms was notably lower than in the control group. Conclusion The study suggests a potential association between ABO blood types and the risk of developing hematological myeloid neoplasms in adolescents and adults. Further research is warranted to elucidate the underlying mechanisms of this relationship.